Efektivitas Peran BPN Dalam Pendaftaran Tanah Yang Kemudian Menimbulkan Persoalan Sertifikat Ganda (Studi Kasus Di Kantor Bpn Kota Kupang ) - Alexsander Reynaldi Koli; Hendrikus Sina Nubae Lolonrian; Vinsensius Samara (LPPM Universitas Sains dan Teknologi Komputer, 2023)
In the land sector, there is a land registration process which from this process allows land rights holders to prove their rights to the land they control. The purpose of land registration in Indonesia is to provide legal certainty (cadastral rechts) of land rights and legal protection of land ownership. Land certificates issued by the National Land Agency (BPN) become proof of legal ownership in any land dispute or all issues concerning land ownership. . The research method that the author uses is an empirical juridical research method. This research uses a problem approach, a statutory approach (Statute-Approach) and a concept approach (conceptual approach). According to Mrs. Wayan Juliati (Interview June 15, 2023) as Head of the Rights Determination and Registration Section at the Kupang City Land Office, in general, certificate checking is an activity carried out to find out physical data and juridical data.